The effect of R&D expenses on earnings and market value - Georgia Pazarzi; John Sorros (SPOUDAI - Journal of Economics and Business, 2018)
The aim of this paper is to examine the effect that Research and Development (R&D) expenditures have on a company's market value and earnings. Prior literature shows that R&D expenses have a positive impact on a firm's market performance, as well as a positive impact on a firm's earnings. The goal of this paper is not only to test the relation between R&D expenses and earnings and between R&D expenditures and market value, but also to prove that this relation changes as time passes. We show that while R&D expenses have an impact on market value in the short-run, their impact on earnings is stronger in the long-run. The sample consists of the companies listed in the North American Stock exchanges for the period 1993-2013 and for the industrial sector. Our results show a positive relation between R&D expenses and market value and between R&D expenses and earnings.
Keywords: M40; M41; M48; 330; R&D expenses; earnings; market capitalization